The Cording Phenotype of Mycobacterium tuberculosis Induces the Formation of Extracellular Traps in Human Macrophages - Kalsum, Sadaf; Braian, Clara; Koeken, Valerie A. C. M.; Raffetseder, Johanna; Lindroth, Margaretha; van Crevel, Reinout; Lerm, Maria (Frontiers in Cellular and Infection Microbiology, 2017)
The causative agent of tuberculosis, Mycobacterium tuberculosis, shares several characteristics with organisms that produce biofilms during infections. One of these is the ability to form tight bundles also known as cords. However, little is known of the physiological relevance of the cording phenotype. In this study, we investigated whether cord-forming M. tuberculosis induce the formation of macrophage extracellular traps (METs) in human monocyte-derived macrophages. Macrophages have previously been shown to produce extracellular traps in response to various stimuli. We optimized bacterial culturing conditions that favored the formation of the cord-forming phenotype as verified by scanning electron microscopy. Microscopy analysis of METs formation during experimental infection of macrophages with M. tuberculosis revealed that cord-forming M. tuberculosis induced significantly more METs compared to the non-cording phenotype. Deletion of early secreted antigenic target-6 which is an important virulence factor of M. tuberculosis, abrogated the ability of the bacteria to induce METs. The release of extracellular DNA from host cells during infection may represent a defense mechanism against pathogens that are difficult to internalize, including cord-forming M. tuberculosis.